2016
DOI: 10.1246/bcsj.20160228
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Gold(III) Hydroxide and Determination of Its Solubility

Abstract: A representative gold(III) complex ion ([AuCl4]−), successively hydrolyzes to form [AuCl4−n(OH)n]− (n = 0–4) in aqueous solution as the pH increases and, finally, precipitates. It has been referred to as “gold(III) hydroxide” for the past fifty years. However, whether the precipitate is gold(III) hydroxide (Au(OH)3) or hydrous gold(III) oxide (Au2O3·nH2O) has remained uncertain. Few studies have been conducted to determine its chemical and physical properties. The aim of this investigation is to identify the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Actually, gold(III) precipitations in alkaline media have been shown to correspond to Au(OH) 3 but not Au 2 O 3 •nH 2 O according to X-ray diffraction, transmission electron microscopy, Au Mossbauer spectroscopy, X-ray absorption spectroscopy, and thermogravimetry/differential thermal analysis studies. 39 It is interesting to note that the reduction potential difference of αand β-oxide is roughly 0.13 ± 0.01 V in both acid and alkaline solutions but becomes more than 0.4 V under neutral conditions (0.42 V at pH 6.8). Therefore, RDE experiments were conducted with varying rotation rates (Figure 3b).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Actually, gold(III) precipitations in alkaline media have been shown to correspond to Au(OH) 3 but not Au 2 O 3 •nH 2 O according to X-ray diffraction, transmission electron microscopy, Au Mossbauer spectroscopy, X-ray absorption spectroscopy, and thermogravimetry/differential thermal analysis studies. 39 It is interesting to note that the reduction potential difference of αand β-oxide is roughly 0.13 ± 0.01 V in both acid and alkaline solutions but becomes more than 0.4 V under neutral conditions (0.42 V at pH 6.8). Therefore, RDE experiments were conducted with varying rotation rates (Figure 3b).…”
Section: Resultsmentioning
confidence: 96%
“…From a comparison of cyclic voltammograms at different pH (Figure a), the β-peak therefore most likely corresponds to the reduction of Au­(OH) 3 . Actually, gold­(III) precipitations in alkaline media have been shown to correspond to Au­(OH) 3 but not Au 2 O 3 • n H 2 O according to X-ray diffraction, transmission electron microscopy, Au Mössbauer spectroscopy, X-ray absorption spectroscopy, and thermogravimetry/differential thermal analysis studies …”
Section: Resultsmentioning
confidence: 99%
“…Thus, Kawamoto et al prepared Au(OH)3 and examined its chemical properties. Consequently, Au(OH)3 was found to be a suitable standard material for Au(III) in the measurement of Au L3-edge XAS data, 39 and Au(OH)3 is now used as a reference standard for Au(III). 36 4•5 What is the driving force for the adsorption of Au(III) complex ions on metal oxides and hydroxides?…”
Section: •4 Standard Materials For the Analysis Of Au(iii) Complexes For Au L3-edge Xas Measurementsmentioning
confidence: 99%
“…It was found that the gold oxides do not decompose in these acid solutions at the same concentration as that of the hydrochloric acid solution. Therefore, it is believed that a water-soluble tetrachloroauric acid (H[AuCl4]) [34][35][36] is produced by the reaction of the gold oxide and the hydrochloric acid in the solution. Decomposition of gold oxides was also observed in 1.1×10 −3 and 1.1×10 −2 M hydrobromic acid solutions using XPS.…”
Section: Reaction Properties Of Gold Oxides In Aqueous Hydrochloric Amentioning
confidence: 99%
“…The gold oxide layer (0.65 nm thick) was found to decompose in a 1.0×10 −2 M aqueous sodium hydroxide solution and it decomposed completely after 22 min at room temperature.Decomposition of gold oxides was also observed in 1.0×10 −3 and 1.0×10 −2 M potassium hydroxide solutions using XPS. Gold hydroxide (Au(OH)3) nanoparticles were prepared from an aqueous solution of tetrachloroauric acid (H[AuCl4]) by raising the solution pH and the precipitate structure was characterized by electron microscopy, Mössbauer spectroscopy, X-ray analysis, and thermal analysis 36. The water solubility of Au(OH)3 at room temperature was reported to be 1.20 mg/100 g of H2O.…”
mentioning
confidence: 99%